Change in Latent Gray-Matter Structural Integrity Is Associated With Change in Cardiovascular Fitness in Older Adults Who Engage in At-Home Aerobic Exercise - Polk, Sarah E.; Kleemeyer, Maike M.; Köhncke, Ylva; Brandmaier, Andreas M.; Bodammer, Nils C.; Misgeld, Carola; Porst, Johanna; Wolfarth, Bernd; Kühn, Simone; Lindenberger, Ulman; Wenger, Elisabeth; Düzel, Sandra (Frontiers in Human Neuroscience, 2022)
In aging humans, aerobic exercise interventions have been found to be associated with more positive or less negative changes in frontal and temporal brain areas, such as the anterior cingulate cortex (ACC) and hippocampus, relative to no-exercise control conditions. However, individual measures such as gray-matter (GM) probability may afford less reliable and valid conclusions about maintenance or losses in structural brain integrity than a latent construct based on multiple indicators (see also Kühn et al., 2017, Köhncke et al., 2021). Here, we established a latent factor of GM structural integrity based on GM probability assessed by voxel-based morphometry, magnetization transfer ratio, and mean diffusivity. Based on this latent factor, we investigated changes in structural brain integrity during a six-month exercise intervention in brain regions previously reported in studies using volumetric approaches. Seventy-five healthy, previously sedentary older adults aged 63 to 76 years completed an at-home intervention study in either an exercise group (n = 40) or in an active control group (n = 35). Measures of peak oxygen uptake (VO2peak) taken before and after the intervention revealed a group-by-time interaction, with positive average change in the exercise group and no reliable mean change in the active control group. Significant group differences in structural brain integrity changes were observed in the right and left anterior cingulate cortex (ACC), right posterior cingulate cortex (PCC), and left juxtapositional lobule cortex (JLC). In all instances, average changes in the exercise group did not differ reliably from zero, whereas average changes in the active control group were negative, pointing to maintenance of structural brain integrity in the exercise group, and to losses in the active control group. Significant individual differences in change were observed for right ACC and left JLC. Following up on these differences, we found that exercising participants with greater fitness gains also showed more positive changes in structural integrity. We discuss the benefits and limitations of a latent-factor approach to changes in structural brain integrity, and conclude that aerobic fitness interventions are likely to contribute to brain maintenance in old age.